Current situation analysis of solar PV waste management in India. (2022) - Sheoran, Manisha; Kumar, Pancham; Sharma, Susheela; Bukya, Mahipal
Abstract: Due to the current situation of coal extinction and over exploitation across the world. The energy demands of the world are to be fulfilled by the renewable energy sources. Among this solar energy has the maximum potential to be exploited to the maximum level to full fill the energy demands of the world. Since ages Sun has been praised as vitalizer of life. Per year 5000 trillion kWh energy falls on the India and most of the parts receive 4–7 kWh per sq. m per day. India has huge robustness for solar energy harnessing power. Solar energy is the most secure and ubiquitous source of energy to meet the power needs after coal exploitation. The growing installations of solar panels will lead to increased waste management. The paper presents core reality of existing solar waste management in India and barriers obstructing the managerial policy. DPSIR approach is utilized to effectively manage the end life of the solar panels. Comparative analysis between existing solar waste management policies in India and other countries across the globe has been established. Solar waste management strategies across the world have been evaluated and solar waste management policy has been proposed here for India. Further the operating success of the proposed policy has been evaluated on the basis of vigor, vulnerability, convenience and risk involved for future prospects. Utmost vigor and outcome of the proposed policy will be observed if they are implanted on every niche of waste generation through all collaborators.